Activation of the Calcium Sensing Receptor Decreases Secretagogue-Induced Fluid Secretion in the Rat Small Intestine - Barahona, Maria J.; Maina, Renee M.; Lysyy, Taras; Finotti, Michele; Caturegli, Giorgio; Baratta, Vanessa; D’Amico, Francesco; Mulligan, David; Geibel, John P. (Frontiers in Physiology, 2019)
Background: The calcium-sensing receptor (CaSR) has been localized and characterized in numerous tissues throughout the body. In the mammalian gastrointestinal tract, the CaSR is known to act as a nutrient sensor and has recently been found to play a role in intestinal fluid and electrolyte balance. This study aims to demonstrate the functionality of the CaSR as a modulator of fluid secretion and absorption along the small intestine. Methods: Small intestine regions (proximal, middle, and distal) were isolated from Sprague Dawley rats and loaded into an ex vivo intestinal perfusion device that provides independent intraluminal and extraluminal (serosa/basolateral) perfusion. The regions were perfused with 5 mM and 7 mM of Ca2+, both in the presence and absence of forskolin (FSK), a potent secretagogue. Control experiments were conducted with intraluminal perfusate containing standard Ringer-HEPES buffer with a physiological concentration of Ca2+ (1 mM). A second set of comparison experiments was performed with intraluminal perfusates containing AC-265347, a CaSR activator and agonist, in the presence of FSK. In all experimental conditions, the intraluminal perfusate contained fluorescein isothiocyanate (FITC)-inulin, a nonabsorbable fluorescent marker of secretion and/or absorption. Intraluminal fluorescence signal was utilized as a measure of water movement at the start of the experiment and every 15 minutes for 90 minutes. Results: Under physiological conditions, increasing the concentration of Ca2+ in the luminal perfusate reduced intestinal fluid secretion in all regions. At a Ca2+ concentration of 7 mM, net fluid absorption was observed in all regions. In the presence of FSK, 5 mM Ca2+significantly decreased fluid secretion and 7 mM Ca2+ abolished FSK-induced fluid secretion. Intraluminal perfusion with 5 mM Ca2+ was as effective as AC-265347, in reducing secretagogue-induced fluid hypersecretion in the proximal and middle regions. Conclusion: This study concludes that apical CaSR is active along the small intestine. Its activation by Ca2+ and/or calcimimetics reduces fluid secretion in a dose-dependent manner, with higher Ca2+ concentrations, or application of a calcimimetic, leading to fluid absorption. We furthermore show that, in the presence of FSK, receptor activation abates FSK secretagogue-induced fluid secretion. This presents a new therapeutic target to address secretory diarrheal illnesses.